AXL/AKT axis mediated-resistance to BRAF inhibitor depends on PTEN status in melanoma - Zuo, Qiang (Oncogene, 2018)
Multiple genetic mutations within melanoma not only cause lesion-specific responses to targeted therapy but also alter the molecular route of resistance to that therapy. Inactivation of PTEN occurs in up to 30% of melanomas, frequently with a concurrent activating BRAF mutation. PTEN loss regulates both acquired and intrinsic drug resistance. Here we show that AXL/AKT axis mediated-resistance to BRAF inhibitor (BRAFi) depends upon PTEN status in melanoma. Hyperactivation of both ERK and AKT pathways was associated with BRAFi resistance in melanoma with wildtype PTEN. The PTEN-impaired melanoma cells required only the ERK resistance mechanism. Moreover, we identified AXL as a key upstream effector of AKT pathway-associated resistance to BRAFi in melanoma with wildtype PTEN, but not in melanoma with impaired PTEN. Notably, we confirmed that blocking AXL by shRNA and a small molecular inhibitor could rescue the sensitivity of resistant melanoma cells with wildtype PTEN to BRAFi and inhibit their growth in vitro and in vivo. Our study has uncovered a mechanism by which PTEN status contributes to acquired resistance to BRAFi and offers a rational strategy to guide clinical testing in pre-identified subsets of patients who relapse during treatment with BRAFi. The identified protein AXL represents a promising therapeutic target for BRAF mutant melanoma patients with wildtype PTEN.